Enhancing the Competence of Karang Taruna Through Socialization of AI (Artificial Intelligence) Usage in Patengan Village, Rancabali District, Bandung Regency - Khairul Arifin, Rifqi; Ariesmansyah, Andre (Jurnal Pengabdian Masyarakat Formosa, 2024)
The Enhancement of Karang Taruna Competence Through the Socialization of AI (Artificial Intelligence) Usage in Patengan Village, Rancabali District, Bandung Regency is expected to be one of the efforts to tackle online violence and cybercrime in the community. It aims to improve information technology skills, making participants more innovative in social and economic empowerment through digital transformation, thereby fostering self-reliance and increasing productivity. The focus of the activity is Karang Taruna, a non-partisan youth development organization that grows based on social awareness and responsibility, by, for, and from the community, especially the youth in the village or equivalent social community. The problem faced by the partners is the lack of understanding among the Karang Taruna youth regarding the utilization of AI and the safe use of the internet. Based on the situation analysis, the target outcome is to enhance the knowledge, understanding, and skills about the importance of AI utilization to equip the youth of Karang Taruna in Patengan Village with knowledge and skills relevant to the latest technological developments, so they can be better prepared to face future challenges.